Archaeology of the Mediterranean during late antiquity and the Middle Ages - Castrorao Barba, Angelo, 1983-; Tanasi, Davide, 1974-; Miccichè, Roberto (University Press of Florida, 2023)
"This book presents multidisciplinary perspectives on Greece, Corsica, Malta, and Sicily from the fourth to the thirteenth centuries, an often-overlooked time in the history and archaeology of the central Mediterranean"--